2007
DOI: 10.1002/edn.93
|View full text |Cite
|
Sign up to set email alerts
|

How to write an abstract

Abstract: BackgroundA scientific abstract is a shortened version of a scientific paper. It is, aside from the title, the most frequently read and most easily accessed portion of an article reporting original scientific research. 1 Often, readers of a scientific journal will only read the abstract, choosing to read at length those papers that are most interesting to them. For this reason, and because abstracts are frequently made available to readers by various computer abstracting services, this section should be writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Ebrahimi & Chan (2015), who compared abstracts in applied linguistics to those in economics, claim that the writer's discipline sometimes informs the structure of abstract writing. Vrijhoef & Steuten (2007) report that many journals do not provide adequate guidelines of abstract writing and thus many of them contain unstructured abstracts. They also report that some medical publications either contain inconsistent data or do not process the data given in abstracts.…”
Section: Discussionmentioning
confidence: 99%
“…Ebrahimi & Chan (2015), who compared abstracts in applied linguistics to those in economics, claim that the writer's discipline sometimes informs the structure of abstract writing. Vrijhoef & Steuten (2007) report that many journals do not provide adequate guidelines of abstract writing and thus many of them contain unstructured abstracts. They also report that some medical publications either contain inconsistent data or do not process the data given in abstracts.…”
Section: Discussionmentioning
confidence: 99%
“…A literature analysis differs from a systematic review in that complete text screening is only carried out when essential [47]. Since the abstracts of original papers are informative and accurate [48], they can concisely and clearly describe one's work; therefore, this study utilised the abstracts of the collected papers to conduct the literature analysis. For this reason, we refer to the first two steps of this method for data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the abstract must be consistent with the rest of the paper; as basic as this instruction might sound, it is not to be taken for granted. For example, a study by Vrijhoef and Steuten [ 56 ] revealed that 18–68% of 264 abstracts from some scientific journals contained information that was inconsistent with the main body of the publications.…”
Section: Structuring the Review Articlementioning
confidence: 99%